PENGARUH SIKAP APATIS MAHASISWA TERHADAP ORGANISASI HIMPUNAN PROGRAM STUDI PPKn UNIVERSITAS SRIWIJAYA - Erry Pebriano; Sri Artati Waluyati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the influence of student apathy on the Civic Education Study Program Organization (HMPPKn) at Sriwijaya University. Apathy among students has emerged as a critical challenge to the sustainability of student organizations, particularly in declining active participation and collective spirit. This research adopts a descriptive quantitative approach using proportionate stratified random sampling, involving 113 respondents from the 2023 and 2024 student cohorts. Data were collected using a Guttman-scale questionnaire and analyzed through simple linear regression. The results reveal a significant influence between student apathy and organizational involvement. The study identifies three main indicators of apathy: the inability to acknowledge personal responsibility, a sense of insecurity and perceived threat, and absolute acceptance of authority without critical challenge. These attitudes negatively affect organizational dynamics, such as low participation in activities, poor leadership initiative, and a weakened sense of belonging. The findings highlight the need for structured efforts by the study program and organization leaders to foster collective awareness, enhance motivation for engagement, and build an inclusive and supportive environment. Thus, strengthening character education and civic values is a vital strategy to mitigate student apathy in academic organizations.